Porphyromonas gingivalis and IgG1 and IgG2 subclass antibodies in patients with juvenile idiopathic arthritis (2017)
Purpose: The purpose of this study was to evaluate the periodontal status and the presence and concentration of Porphyromonas gingivalis (P. gingivalis) and immunoglobulin G (IgG) subclass against P. gingivalis in juvenile idiopathic arthritis (JIA) and its association with rheumatic clinical activity parameters. Methods: Rheumatologic conditions and periodontal status were clinically assessed in 51 patients with JIA. P. gingivalis, IgG1 and IgG2, high-sensitivity C-reactive protein, erythrocyte sedimentation rate, rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPAs), and human leukocyte antigen B27 were also evaluated. Results: Periodontitis was observed in 21.5 percent of the patients, 23.5 percent of whom were positive for P. gingivalis, which was associated with enthesitis-related arthritis (P<0.035). IgG1 against P gingivalis was associated with RF autoantibodies (P=0.05), and all patients positive for ACPAs had higher anti-P gingivalis IgG1 levels. A significant correlation was found between the presence of limited joint mobility and the plaque index in polyarticular JIA (r=0.55, P=0.028). Conclusions: An association between IgG and rheumatic disease activity markers in JIA was evident. It is important to investigate the familiar periodontal status and clinical course in JIA, especially in enthesitis-related arthritis.